1990
DOI: 10.1210/endo-126-6-3223
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Progesterone-Binding Breast Cyst Protein GCDFP-24 Secretion by Estrogens and Androgens in Human Breast Cancer Cells: A New Marker of Steroid Action in Breast Cancer*

Abstract: We have previously demonstrated that androgens are potent inhibitors of breast cancer cell proliferation under both basal and estrogen-induced incubation conditions, while they suppress expression of the estrogen and progesterone receptors. To better understand the mechanisms responsible for the antagonism between androgens and estrogens in breast cancer and to obtain a new tumor marker for the actions of these two steroids, we have investigated the effects of androgens and estrogens on expression of the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
3

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 39 publications
1
59
0
3
Order By: Relevance
“…Because testosterone and progesterone were shown to up-regulate and estradiol to downregulate ZAG, apoD and GCDFP-15 in breast cancer cell cultures [11][12][13][14][15][16], we hypothesized that levels of these hormones might be significant predictors for NAF protein profiles. However, no differences in levels of testosterone and progesterone were detected, and only estradiol was marginally higher in type I compared to type II secretors (P=0.08) in univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because testosterone and progesterone were shown to up-regulate and estradiol to downregulate ZAG, apoD and GCDFP-15 in breast cancer cell cultures [11][12][13][14][15][16], we hypothesized that levels of these hormones might be significant predictors for NAF protein profiles. However, no differences in levels of testosterone and progesterone were detected, and only estradiol was marginally higher in type I compared to type II secretors (P=0.08) in univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of type I NAF proteins has been studied in cultures of malignant mammary epithelial cells. In these cultures, androgens (dihydrotestosterone or fluoxymesterone) stimulated the secretion of ZAG, apoD and GCDFP-15 into the culture media [11][12][13][14], progesterone and prolactin up-regulated GCDFP-15 expression [15,16], and estradiol decreased the synthesis of GCDFP-15 and apoD [12][13][14]. In contrast, Zhou et al showed that testosterone, progesterone, and tamoxifen decreased apoD mRNA expression in the mammary glands of ovariectomized rhesus monkeys [17].…”
Section: Introductionmentioning
confidence: 99%
“…The cellular DNA content was determined with fluorochrome 3,5-diaminobenzoic acid free acid (DABA) as described previously (21,74). To analyze growth curves of HTO cell clones, cells were plated in 24-well plates at an initial density of 3 ϫ 10 3 cells per well and 24 h later were grown in the presence or absence of Dox (2 g/ml).…”
Section: Plasmidsmentioning
confidence: 99%
“…The mechanisms responsible for this marked induction of apoD mRNA by retinoids are presently unknown. However, it seems likely that their elucidation could contribute to clarify the role of these compounds in the biochemical path-ways leading to apoD-increased expression in specific conditions, such as growth arrest and cell differentiation of breast cancer cells, as well as in peripheral nerve regeneration processes (11,12,21,22).…”
Section: Apolipoprotein D (Apod)mentioning
confidence: 99%